PROBLEM EPISTEMOLOGY CHATGPT: WORLDVIEW ISLAM PERSPECTIVE SYED MUHAMMAD NAQUIB AL-ATTAS - Bramantyo Suryo Nugroho; Muchammad Taufiq Affandi; Imron Rosyadi; Isman; Muthoifin (Universitas Muhammadiyah Surakarta, 2023)
This study discusses a comparison between the Islamic worldview, which emphasizes religious authority and intuition as sources of knowledge, and the contemporary worldview which focuses more on rationalism and empiricism. From the Islamic perspective, the tradition of